2020 30th International Conference on Field-Programmable Logic and Applications (FPL) 2020
DOI: 10.1109/fpl50879.2020.00044
|View full text |Cite
|
Sign up to set email alerts
|

Precise Pointer Analysis in High-Level Synthesis

Abstract: Pointer analysis computes the set of memory locations that each pointer access can point to during hardware runtime. The more sensitive the pointer analysis, the more precise these sets are likely to be, reducing unnecessary sharing of memory resources between instructions during high-level synthesis (HLS) memory generation. Despite the importance of precision, modern HLS tools typically sacrifice precision to prioritise quicker analysis times, although there are several pointer analyses that can produce reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Comparison to our prior work. This article extends our conference paper at FPL 2020 [31] in three ways. Firstly, in our conference paper, we identified that the points-to graph supplied to HLS pointer synthesis is often imprecise.…”
Section: Introductionmentioning
confidence: 65%
“…Comparison to our prior work. This article extends our conference paper at FPL 2020 [31] in three ways. Firstly, in our conference paper, we identified that the points-to graph supplied to HLS pointer synthesis is often imprecise.…”
Section: Introductionmentioning
confidence: 65%